Medical Ethics in Clinical Practice in Nepal: Challenges and Way Forward - Raut, Shristi; Kumar, Anand (Journal of Universal College of Medical Sciences, 2018)
Ethics for health care professional have many components. Among them, medical ethics is one of the important but neglected component which deals with issues related to confidentiality, beneficence and non-maleficence between health care providers and stake holders. Four basic principles of medical ethics are autonomy, justice, beneficence and non- maleficence which form the foundation of ethical clinical practice. The level of knowledge on medical ethics that medical students receive during the training is meagre and inadequate. In recent years, clinical practice has become more challenging. This is primarily due to increased opposition, aggression and violence against medical professionals at health care settings. As a result, the gap between clinicians and patients is increasing leading to diminishing trust and real/perceived allegations. In addition, the widening gap between doctors and patients has provided a space for middle men/broker to meddle, oppose and flare up the violence against treatment providers. Doctors and other medical professionals have been increasingly facing such challenges leading to circumspection in their practice, despondence, psychosocial trauma and depression. There is an urgent need of incorporation of medical ethics in undergraduate curriculum and independent hospital ethics committee consisting of experts from the hospital and outside to monitor and provide rational reasons to minimize such challenges.